Impact of acute exposure to ambient PM2.5 on non-trauma all-cause mortality in the megacity Delhi. (15th August 2021) - Joshi, Pallavi; Ghosh, Santu; Dey, Sagnik; Dixit, Kuldeep; Choudhary, Rohit Kumar; Salve, Harshal Ramesh; Balakrishnan, Kalpana
Abstract: Exposure to ambient fine particulate matter (PM2.5 ) is the largest environmental health risk in India. All previous studies in India focused on PM10 exposure for acute impact assessment; even the single study examining the PM2.5 acute exposure impact used data from a single site. Here we estimated the impact of acute PM2.5 exposure on non-trauma all-cause mortality in the megacity Delhi using a quasi-Poisson regression model and satellite-derived high-resolution (1-km) exposure data. Our satellite-PM2.5 dataset was calibrated and validated against coincident measurements from ground-based reference-grade monitors. This allowed us to minimize exposure misclassification, which otherwise would have happened due to reliance on limited ground-based monitoring sites with a large spatial gap. The annual average (median) PM2.5 exposure (with interquartile range) during this period was 108.5 (63.5–133.6) μg/m³. We found a 0.52% (95% confidence interval, CI: 0.42–0.62%) increase in non-trauma all-cause mortality for every 10 μg/m³ increase in 6-days cumulative PM2.5 exposure with a relatively higher impact on men (0.57%, 95% CI: 0.46–0.69%) than on women (0.52%, 0.38–0.65%). The impact of PM2.5 was almost two-fold higher in winter (0.55%, 0.45–0.66%) per 10 μg/m³ increase in PM2.5 than in summer (0.29%, 0.14–0.45%). The district-level aggregated 6-days cumulative PM2.5 exposure had the largest impact on mortality (1.10%, 0.84–1.35%). The impact of acute exposure to PM2.5 on all-cause mortality was larger than that of PM10 exposure (from previous studies). Our study adds to the global evidence pool, fills the critical gap of evidence of acute PM2.5 exposure impact on mortality in India, and most importantly, demonstrates the significance of disaggregated exposure assessment using satellite data to reduce exposure misclassification in health impact studies, particularly in data-poor regions. Main finding: We estimate a 0.52% increase in all-cause mortality for every 10 μg/m³ rise in short-term PM2.5 exposure with a two-fold higher impact in the winter than in the summer and a higher impact on male (0.57%) than on female (0.52%) in the megacity Delhi. Highlights: Novel use of high-resolution (1-km) satellite data to study acute impact of PM2.5 exposure in Delhi. The impact on all-cause mortality is two-fold higher in winter than in summer. Spatially disaggregated exposure of PM2.5 exhibits a higher effect on mortality.